2019
DOI: 10.29244/jppt.v2i1.25315
|View full text |Cite
|
Sign up to set email alerts
|

Biologi Ikan Tongkol Komo (Euthynnus affinis) Di Laut Jawa

Abstract: Ikan tongkol komo (Euthynnus affinis)  termasuk salah satu ikan pelagis ekonomis penting yang tertangkap di Laut Jawa. Data dan informasi tentang  ikan tongkol komo di Laut Jawa masih terbatas, sehingga perlu dilakukan penelitian biologi ikan ini. Penelitian beberapa aspek biologi ikan tongkol komo dilakukan dari bulan Januari sampai Desember 2012. Penelitian ini bertujuan untuk mengetahui beberapa aspek biologi tongkol komo yang meliputi  hubungan panjang dan berat, nisbah kelamin, tingkat kematangan gonad, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…Mackerel tuna (Euthynnus affinis) landed in Idi Rayeuk fishing port during the study have a length of 33 -54 cm with a weight of 0.6 -2.5 kg. These results are in accordance with the research results of Agustina et al (2018), Ekawaty et al (2018), Hidayat et al (2018), which state that tuna length ranged from 24 -71 cm with an average of 51.66 cm and weight 0.21 -7.05 kg with an average of 2.72 kg. The catch of Indian Spanish Mackerel (Scomberomous guttatus) landed at Idi Rayeuk fishing port has a size between 44 -66 cm and a 0.7 -1.7 kg weight.…”
Section: Discussionsupporting
confidence: 93%
“…Mackerel tuna (Euthynnus affinis) landed in Idi Rayeuk fishing port during the study have a length of 33 -54 cm with a weight of 0.6 -2.5 kg. These results are in accordance with the research results of Agustina et al (2018), Ekawaty et al (2018), Hidayat et al (2018), which state that tuna length ranged from 24 -71 cm with an average of 51.66 cm and weight 0.21 -7.05 kg with an average of 2.72 kg. The catch of Indian Spanish Mackerel (Scomberomous guttatus) landed at Idi Rayeuk fishing port has a size between 44 -66 cm and a 0.7 -1.7 kg weight.…”
Section: Discussionsupporting
confidence: 93%
“…50 Year 2017), indicating that the fish is already fully exploited. In addition, studies by Hidayat et al (2019) and Chodrijah et al (2013) also suggested similar results, i.e. kawakawa's length at first capture (Lc) is smaller than its size at first gonadal maturity (Lm), and kawakawa is indeed already fully exploited.…”
mentioning
confidence: 69%
“…The fish has unique characteristics, i.e. oblique, curved black stripes above the ribs and black spots between fin and abdomen (Hidayat et al 2019). It is an important commodity in fishing sector, according to Cantor in (Santos et al 2010).…”
mentioning
confidence: 99%
“…One of the management efforts that can be done is to manage catch selectivity for all fishing gear. Selectivity is defined as the ability of each method or type of fishing gear to capture fish in a certain fraction or part of the population by grouping them based on species, age, size, or behavior of certain fish and removing others [25]. Knowledge of fishing selectivity can be used in fisheries management, primarily regulating the size of the nets and hooks of a fishing vessel to provide the minimum size of fish that can be caught [26].…”
Section: Discussionmentioning
confidence: 99%
“…One of the efforts in fisheries management is to reduce juvenile fish resources that have less than the size at the first maturity of the gonads [27]. Handline operated in FADs is categorized as fishing gear with moderate selectivity compared to Purse Seine [25]. Tuna fisheries management in the Indian Ocean will refer to RFMOs' regulation, IOTC's resolutions, and CMMs.…”
Section: Discussionmentioning
confidence: 99%